Peran English Corner Dalam Meningkatkan Skill Foreign Language Sekolah Menengah Atas Makassar - Basri, Fivi Elvira (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to identify and analyze the challenges of foreign language mastery, particularly English, among high school students in Makassar City, in response to the demands of globalization and international job competition. The method used was a quasi-experimental design with a pre-test and post-test to measure the effectiveness of the English Corner program in English learning. The research subjects were students of SMA Negeri 19 Makassar and SMA Tri Tunggal 45 Makassar who came from diverse socio-economic backgrounds. The results showed that the main obstacles to foreign language mastery were low motivation, limited facilities, lack of language practice, and minimal environmental support. The implementation of the English Corner program in collaboration with universities improved students' language competence, self-confidence, and cultural sensitivity. This study recommends the need for cooperation between schools, communities, and the government in creating a learning environment that supports the sustainable development of foreign languages.